2014
DOI: 10.1371/journal.pone.0088895
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Borrelia Species after Creation of an In-House MALDI-TOF MS Database

Abstract: Lyme borreliosis (LB) is a multisystemic disease caused by Borrelia burgdorferi sensu lato (sl) complex transmitted to humans by Ixodes ticks. B. burgdorferi sl complex, currently comprising at least 19 genospecies, includes the main pathogenic species responsible for human disease in Europe: B. burgdorferi sensu stricto (ss), B. afzelii, and B. garinii. In this study, for the first time, MALDI-TOF MS was applied to Borrelia spp., supplementing the existing database, limited to the species B. burgdorferi ss, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 29 publications
2
26
0
1
Order By: Relevance
“…The Clinprotools software used to support the interpretation of MALDI-TOF MS identifies species-specific peaks as the basis for species identification [30, 41, 49]. In agreement with previous studies [25, 30], we identified specific peaks at 4,410, 5,794, 6,551, 7,553 and 9,713 Da for all B .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The Clinprotools software used to support the interpretation of MALDI-TOF MS identifies species-specific peaks as the basis for species identification [30, 41, 49]. In agreement with previous studies [25, 30], we identified specific peaks at 4,410, 5,794, 6,551, 7,553 and 9,713 Da for all B .…”
Section: Discussionsupporting
confidence: 87%
“…Three statistical tests (Anderson-Darling (AD), t-test/ANOVA (TTA), and Wilcoxon/Kruskal-Wallis (W/KW) are incorporated into Clinprotools and were used to analyse intensity data. All discriminatory peaks that exhibited P-values of <0.01 by any of these statistical test were further evaluated by eye [41] and validated with the peaks of other isolates from the same species. Peaks that were unique to specific species or statistically different in intensity and showed consistent results from three independent experiments were considered as the discriminatory peaks.…”
Section: Methodsmentioning
confidence: 99%
“…The spectra for each viral strain were uploaded in MALDI BioTyper software (version 3.1.66, Bruker Daltonics). The MSP spectrum was calculated in the range 2–11.2 KDa, considering 35 main peaks, by the automated function of BioTyper software (BioTyper MSP Creation Standard Methods) following the manufacturer’s suggestions as previously described2021. The “Preprocessing”, “MSP Creation” and “Subtyping MSP Creation” parameters were set as detailed below.…”
Section: Methodsmentioning
confidence: 99%
“…Despite many literature data about MALDI-TOF MS application in routine clinical microbiology, and in experimental approaches related to bacteria, parasites, yeasts and moulds616171819202122, very few reports are available about its application in virus research and laboratory diagnosis of viral infections6232425. In most of the studies, specific viral genome sequences are previously amplified by PCR and then the amplicons are analysed by MALDI-TOF MS15.…”
mentioning
confidence: 99%
“…[5][6][7] Accordingly, molecular tools can be used to discriminate these different Borrelia. 8,9 Here, using such molecular tools, we detected sequences indicative of a new Borrelia sp.…”
mentioning
confidence: 99%